Penguatan Kesiapan Pra Nikah melalui Edukasi Kesehatan Spiritual - Hidayati, Nur Rahmah; Novanto, Riza Awal; Alipianto, Nurkholik (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Marriage readiness requires not only physical and economic preparedness but also spiritual aspects, which serve as an essential foundation for building a harmonious household. This community service activity aimed to strengthen maturity in preparing for marriage through spiritual health education integrated with biological maturity, specifically targeting individuals of premarital age. The methods used included interactive lectures, followed by group discussions and QA sessions, as well as evaluation through pretests and posttests. The participants of this program were 48 individuals aged 17 to 28 years. The Wilcoxon analysis showed a significant difference before and after the intervention, with the average knowledge score increasing from 83.96 to 94.17. These findings indicate that education based on spiritual values plays a crucial role in equipping the younger generation for marriage preparation. We should develop a sustainable youth development program that strengthens the spiritual aspect to help prevent future household conflicts.